Diagnosis and Management of Infections in Patients with Mendelian Susceptibility to Mycobacterial Disease - Aparna Dalvi; Umair Ahmed Bargir; Gita Natraj; Ira Shah; Manisha Madkaikar (Pathogens, 2024)
The diagnosis and treatment of patients with mendelian susceptibility to mycobacterial disease (MSMD) pose consistent challenges due to the diverse infection spectrum observed in this population. Common clinical manifestations include Bacillus Calmette-Guérin vaccine (BCG) complications in countries where routine BCG vaccination is practiced, while in non-BCG-vaccinating countries, Non-Tuberculous Mycobacteria (NTM) is prevalent. In tuberculosis-endemic regions, Mycobacterium tuberculosis (MTB) has a high prevalence, along with other intracellular organisms. Isolating these organisms presents a significant challenge, and treatment is often initiated without confirming the specific species. This review primarily focuses on the methods and challenges associated with diagnosing and treating MSMD patients.